Artificial maturation of iron- and sulfur-rich Mars analogues: Implications for the diagenetic stability of biopolymers and their detection with pyrolysis gas chromatography–mass spectrometry - Tan,J; Royle,S; Sephton,M (Astrobiology, 2021)
Acidic iron- and sulfur-rich streams are appropriate analogues for the late Noachian and early Hesperian periods of martian history, when Mars exhibited extensive habitable environments. Any past life on Mars may have left behind diagnostic evidence of life that could be detected at the present day. For effective preservation, these remains must have avoided the harsh radiation flux at the martian surface, survived geological storage for billions of years, and remained detectable within their geochemical environment by analytical instrument suites used on Mars today, such as thermal extraction techniques.We investigated the detectability of organic matter within sulfur stream sediments that had been subjected to artificial maturation by hydrous pyrolysis. After maturation, the samples were analyzed by pyrolysis–gas chromatography–mass spectrometry (py-GC-MS) to determine whether organic matter could be detected with this commonly used technique. We find that macromolecular organic matter can survive the artificial maturation process in the presence of iron- and sulfur-rich minerals but cannot be unambiguously distinguished from abiotic organic matter. However, if jarosite and goethite are present in the sulfur stream environment, they interfere with the py-GC-MS detection of organic compounds in these samples. Clay reduces the obfuscating effect of the oxidizing minerals by providing nondeleterious adsorption sites. We also find that after a simple alkali and acid leaching process that removes oxidizing minerals such as iron sulfates, oxides, and oxyhydroxides, the sulfur stream samples exhibit much greater organic responses during py-GC-MS in terms of both abundance and diversity of organic compounds, such as the detection of hopanes in all leached samples.Our results suggest that insoluble organic matter can be preserved over billions of years of geological storage while still retaining diagnostic organic information, but sample selection strategies mu